Set-up of a multi wavelength polar photometer for off-line absorption coefficient measurements on 1-h resolved aerosol samples. (May 2017) - Bernardoni, Vera; Valli, Gianluigi; Vecchi, Roberta
Abstract: In this paper, a polar photometer (PP_UniMI) was set up to measure the aerosol absorption coefficient (σap ) at four wavelengths (λ) on 1-h resolved aerosol samples collected using a streaker sampler. Due to the characteristics of such samples (small deposit area, low aerosol load, and limited substrate thickness − 10 μm), the main technical developments aimed at reaching suitable limits of detection (LODs). To this aim, multiple scattering between the sample and a suitable substrate were exploited to amplify the system sensitivity to absorbing particle load. In the paper, the development and test of this innovative approach is presented. LODs for σap in the range 5.0–11.6 Mm −1 were reached, depending on the wavelength. Such values were suitable for the analysis of 1-hour resolved samples collected at an urban background site in Milan (Italy) during a test campaign of 1-week carried out in winter 2015. The methodology was validated comparing σap measurements performed by PP_UniMI at λ=635 nm on the streaker sample to the data obtained by a Multi-Angle Absorption Photometer (MAAP) operated in parallel. Agreement within 10% was found. To check the results obtained at other wavelengths, Ångström Absorption Exponent (AAE) was calculated from σap measurements at 4-λ. The AAE values resulted in the range of expectations for aerosol emitted by fossil fuel combustion (0.8–1.2) and wood burning (0.9–3.5), which are the main sources contributing to absorbing aerosol in urban areas in winter. The analytical methodology can be extended to samples collected with high time resolution using other high-time resolution samplers (e.g. drum rotating impactors). This is – as far as we know – the first time that σap measurements are performed on streaker samples collected with 1-h resolution. Our results thus set PP_UniMI as an important tool for the community performing high time resolved sampling to widen the characterisation of such samples and to further develop source apportionment studies. Highlights: Set-up of a polar photometer to analyse high time resolved samples. 4-λ optical absorption coefficient measurement on filter-sampled aerosol. Innovative methodology exploiting sample-substrate multiple scattering. Provides data for source apportionment applications.